MORICANDIA Arvensis: A MULTIFUNCTIONAL MEDICINAL PLANT WITH BROAD BIOLOGICAL ACTIVITIES: PHYTOCHEMICAL CONTENT, POTENTIAL ANTIOXIDANTS, ANTI-HEMOLYTIC AND ANTIMITOTIC INVESTIGATION - Farid Berroukeche; Naouel Atoui; Fethi Toul; Serra Djaaboub (Journal of Animal and Plant Sciences, 2026)
Moricandia arvensis is a flowering plant of the Brassicaceae family. Its richness of flavonoid glycosides, such as kaempferol and quercetin derivatives, contribute to many biological properties.This study evaluates the phytochemical composition and in vitro biological activities of ethanolic and acetonic extracts from Moricandia arvensis leaves and flowers. Phytochemical screening revealed the presence of tannins, terpenoids, alkaloids, sterols, reducing compounds, and starch, highlighting the chemical richness of this species. Antioxidant activity assessed by the DPPH scavenging assay demonstrated that the acetonic flower extract exhibited the highest activity (IC50 = 6.44 ± 0.89 mg/mL), which was 21% to 89 % higher compared to other extracts, respectively; however, it remained considerably weaker than the standard antioxidant ascorbic acid (IC50 = 1.67 ± 0.051 mg/mL). Anti-hemolytic analysis indicated that the ethanolic flower extract increased erythrocyte membrane protection by approximately 30% relative to the acetonic extract, achieving up to 60% protection at 0.5 mg/mL. The Allium cepa mitotic model revealed that the acetonic leaf extract reduced the mitotic index by around 65% compared to the untreated control and marginally exceeded colchicine (60%) in mitotic inhibition. Notably, the prophase arrest induced by the extract contrasted with colchicine’s metaphase arrest, suggesting a distinct cytological mechanism. Overall, M. arvensis exhibited moderate anti-hemolytic and pronounced antimitotic effects, but antioxidant capacity was relatively weak. These quantitative findings contribute valuable insights into the biological properties of M. arvensis extracts and provide a foundation for future studies focused on bioactive compound isolation and further pharmacological investigation.
Keywords: Moricandia arvensis; DPPH scavenging; Allium cepa assay; anti-hemolytic activity